Can MOOCs empower people to critically think about climate change?: a learning outcome based comparison of two MOOCs - Otto, Daniel (2020)
Climate change can be regarded as one of the key topics of sustainable development where public awareness and education are crucial. In the field of education, Massive Online Open Courses (MOOCs) have raised remarkable attention throughout the last decade as their initial objective is to provide massive open online education for everyone. This article aims to explore the impact of MOOCs on learning about climate change. This is necessary in order to evaluate whether MOOCs can make a substantial contribution to lifelong learning about sustainable development for a wider audience. We therefore present findings from self-assessment questionnaires of participants from two climate change MOOCs provided by two-distance learning universities in Germany and Portugal. Both MOOCs aimed at imparting to the participants the competencies to better understand the topic of climate change. The objective of the survey was a competency-based evaluation to review which learning outcomes have been achieved. The results indicate that taking part in either of the MOOCs increased the participants’ competencies to critically engage in the climate change debate. MOOCs are able to convey certain learning outcomes to the students and thus can contribute to climate change literacy. For further research, we recommend a more differentiated view on MOOCs and the learning opportunities for participants. Options for potential improvement are to think of better ways of how to integrate MOOCs into climate change education or to consider possibilities to increase the attractiveness of MOOCs for instance by using innovative formats to overcome the barriers between formal and informal learning